Single-nucleotide polymorphisms in DNA-repair genes and cutaneous melanoma - Figl, Adina; Scherer, Dominique; Nagore, Eduardo; Lorenzo Bermejo, Justo; Botella-Estrada, Rafael; Gast, Andreas; Thirumaran, Ranjit Kumar; Planelles, Dolores; Hemminki, Kari; Schadendorf, Dirk; Kumar, Rajiv (Mutation research. Genetic toxicology and environmental mutagenesis, 2010)
Single-nucleotide polymorphisms in different DNA-repair genes are reported to modulate risk of various cancers including melanoma. We genotyped DNA from 1186 melanoma patients and 1280 healthy controls for 13 different polymorphisms in eight DNA-repair genes. Data analyses showed that none of the polymorphisms except T241M XRCC3 was associated with an increased risk for cutaneous melanoma. Carriers of the variant alleles were associated with a decreased risk (OR 0.83; 95% CI, 0.79-0.98). Three additional polymorphisms together with T241M XRCC3 that tagged the entire gene region and the neighbouring genes KLC1, ZFYVE21 and PPP1R13B were not associated with the disease risk; neither were the inferred haplotypes. Imputation showed association of comparable magnitude with 11 non-genotyped neighbouring polymorphisms. Finally, the combination of results for all polymorphisms genotyped in the present study with published data suggests that none of the investigated polymorphisms was associated with melanoma susceptibility. We conclude that 13 non-synonymous polymorphisms in eight DNA-repair genes that are frequently investigated with respect to modulation of cancer risk in populations are not associated with susceptibility to cutaneous melanoma.